MENCARI ALTERNATIF SISTEM PEMILUKADA YANG EFEKTIF, EFISIEN DAN DEMOKRATIS - Lita Tyesta ALW (Faculty of Law, Universitas Diponegoro, 2012)
Abstract Since the prevailing of Act No. 32 of 2004 there has been a change in filling the position of head of region, which was originally made ​​by Parliament to be a direct election by the people. In a direct local elections, there are several systems in use, the system of one round (first past the post system), system of two rounds (two round system), and mixed systems (preferential vote). Where each system has its advantages and disadvantages, because there is no one perfect system. However if desired the local elections are more effective and efficient, then the mixed system (preferential vote) is considered more appropriate, because with only one round is to ensure the legitimacy of the people, saving cost, implementation time is not long, post-election political climate quickly subsided, and the local people can quickly find out who the head region is, so that the immediate implementation of the government and the wheels of government running normally again. Keywords : effective, efiesien, and democratic election system. Abstrak Sejak berlakunya UU Nomor 32 Tahun 2004 telah terjadi perubahan dalam pengisian jabatan kepala daerah, yang semula dilakukan oleh DPRD menjadi pemilihan langsung oleh rakyat.Pada pemilihan kepala daerah langsung terdapat beberapa sistem yang digunakan, yaitu sistem satu putaran (first past the post system); sistem dua putaran (two round system), dan sistem campuran (preferential vote). Masing-masing sistem memiliki kelebihan dan kelemahan, karena tidak ada satu system pun yang dapat berlaku sempurna. Namun demikian apabila dikehendaki adanya pemilihan kepala daerah yang lebih efektif dan efisien, maka sistem campuran (preferential vote) dinilai lebih sesuai, karena dengan satu putaran saja sudah menjamin legitimasi rakyat, penghematan biaya, waktu pelaksanaan tidak lama, suhu politik pasca pemilukada cepat mereda, dan rakyat daerah secara cepat dapat mengetahui siapa kepala daerahnya, sehingga pelaksanaan pemerintahan segera berjalan dan roda pemerintahan normal kembali. Kata kunci : sistem pemilukada yang efektif, efiesien dan demokratis.